Synthesis and crystal structure of N1-tosylacetylamidrazone - Hamzaoui, Salwa; Salah, Bochra Ben; Rekik, Awatef; Kossentini, Mohamed (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The condensation of two molar equivalents of N1-tosylhydrazonate 1 with one molar equivalent of 1,2-diaminoethane give birth to amidrazone in good yields. The structure of the synthesized compound was identified by X-ray diffraction, IR spectroscopy and nuclear magnetic resonance.Â